Earnings management through accretive share buyback and share price return - Chandren, Sitraselvi; Ahmad, Zamri; Ali, Ruhani (2015)
This study examines the relationship between earnings management through accretive share buyback and share price return of 220 Malaysian listed firms from year 2001 to 2008.The objective of this study is to determine the market behavior on those firms that made good earnings news announcement through accretive share buyback.The 5 days Cumulative Abnormal Return (CAR) result shows that these firms earn positive share price return immediately after the earnings announcement day.Further, the regression result reports on the existence of positive effect of accretive share buyback on share price return.Basically, firms which announce good earnings news by meeting or beating EPS forecast through accretive share buyback earn positive share price return. In sum, investors reward firms that made positive earnings surprises or good earnings news. The good earnings news announcement is a challenge for firms in the capital market for a positive financial health and future prospect.Earnings management through accretive share buyback plays a role to achieve the good earnings news.This paper contributes on the market behavior or investors reaction on firms that deliver good earnings news through accretive share buyback.